Evaluation of the ‘Live Life Better Service’, a community-based weight management service, for morbidly obese patients - Wallace, Dean; Myles, Puja; Holt, Rachel; Nguyen-Van-Tam, Jonathan S. (Oxford University Press, 2016)
Background